Structural Contradictions Between Energy Production and Consumption Along With Economic Development and Environmental Protection in China: Evidence and Policy Implications - Tang, Erzi (Frontiers in Environmental Science, 2022)
This paper empirically describes and analyzes the structural contradictions between energy production and consumption in the Chinese local economy. With the rapid economic growth, energy usage in China increased gradually and exceeded energy production in a long time. For some detailed energy such as petroleum, the gap between supply and demand is relatively larger than that of the whole energy sector in the economy. The process of turning fossil fuels into final energy products for use will cause a great deal of pollution, especially emitting industrial waste gases, such as particulate matter emission, into the atmospheric environment. Increased energy production directly and greatly to solve the gap between energy supply and demand in the economy may impact environmental quality and not meet the sustainable development needs. It is difficult to coordinate energy production and consumption when considering economic development and environmental protection in economic operation. Import energy could meet the excess energy consumption in a short period but often fluctuates from foreign energy market change and some political events. For policy recommendations, some policies which directly decline energy consumption may impact economic development since mainly the industry sector uses energy, and industrial production is an important component of GDP in China. Declining the role of industry sector in the economy and reducing industrial products export, including some energy intensive products, could solve the structural contradictions between energy production and consumption under the condition of maintaining economic development and protecting the environment in China, but this is a long-term adjustment process.